Perception of verticality in the post-COVID-19 condition correlates to infection severity - Fonseca, Bruno Henrique de Souza; de Andrade, Pedro Henrique Sousa; Henrique, Maria Eduarda Salum Aveiro; Baggio, Jussara Almeida de Oliveira; Bazan, Rodrigo [UNESP]; de Souza, Luciane Aparecida Pascucci Sande; Luvizutto, Gustavo José (SAGE Publications, 2023)
Background: SARS-CoV-2 infection affects multiple systems, including musculoskeletal, neurological, and respiratory systems. Changes associated with physical inactivity due to prolonged hospitalization can affect the functional capacity of individuals with long coronavirus disease 2019 (COVID-19) or post-COVID-19 condition and may cause changes in some postural control functions, such as verticality. Objectives: This study aimed to evaluate the perception of verticality in individuals with long COVID. Design: Cross-sectional study Methods: This study included 60 participants with post-COVID-19 condition divided into 2 groups: hospitalized group (n = 24), those hospitalized owing to SARS-CoV-2 infection; and non-hospitalized group (n = 36), those infected with SARS-CoV-2 but not hospitalized. All participants were examined using a post-COVID-19 functional status (PCFS), sit-to-stand test, grip strength assessment, painful and tactile sensory assessments, visual acuity assessment, and vestibular assessment. Verticality perception was evaluated using the subjective visual vertical (SVV) and subjective haptic vertical (SHV) tests. In both tests, the absolute values (positive values only) and true values (positive and negative values) were considered. To verify potential confounders that could influence the verticality of the results, logistic regression models were used for categorical variables and multiple linear regressions were used for continuous variables. For analysis between groups, the independent samples test (Mann–Whitney U test) was used. Results: There were no confounders between clinical variables and verticality in either group. There was a significant increase in absolute SVV (mean deviation [MD]: 2.83; P <.0001) and true SVV (MD: −4.18; P =.005) in the hospitalized group compared to the non-hospitalized group. Furthermore, there was a significant increase in the true SHV (MD: −3.6; P =.026) in the hospitalized group compared to that in the non-hospitalized group. Conclusion: Less accurate visual and haptic verticality perception task performance was observed in hospitalized patients with post-COVID-19 condition.
Keywords: COVID-19; haptic vertical subjective; SARS-CoV-2; subjective visual vertical; verticality